2022
DOI: 10.3390/healthcare10071288
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Method Evaluation of a Community Pharmacy Antimicrobial Stewardship Intervention (PAMSI)

Abstract: The community pharmacy antimicrobial stewardship intervention (PAMSI) is multi-faceted and underpinned by behavioural science, consisting of the TARGET Antibiotic Checklist, staff e-Learning, and patient-facing materials. This mixed-method study evaluated the effect of PAMSI on community pharmacy staffs’ self-reported antimicrobial stewardship (AMS) behaviours. Data collection included staff pre- and post-intervention questionnaires, qualitative interviews, and TARGET Antibiotic Checklists. Quantitative data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In England, this prompted the development of PAMSI which incorporated the pharmacy AMS e-Learning module, the TARGET Antibiotic Checklist and other educational resources for patients. An evaluation of PAMSI in 2019 and 2020 found that community pharmacy staff reported better understanding of AMR and their AMS role, as well as the confidence to provide self-care and adherence advice to patients, and to discuss clinical aspects of prescriptions with prescribers where needed [ 9 , 10 ]. These findings led to the national scale up and implementation of the revised AMS e-Learning module as well as the Antibiotic Guardian campaign through the PQS in 2020/21, which was an important first step to ensure the workforce had the necessary capabilities before introducing the TARGET Antibiotic Checklist the following year.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In England, this prompted the development of PAMSI which incorporated the pharmacy AMS e-Learning module, the TARGET Antibiotic Checklist and other educational resources for patients. An evaluation of PAMSI in 2019 and 2020 found that community pharmacy staff reported better understanding of AMR and their AMS role, as well as the confidence to provide self-care and adherence advice to patients, and to discuss clinical aspects of prescriptions with prescribers where needed [ 9 , 10 ]. These findings led to the national scale up and implementation of the revised AMS e-Learning module as well as the Antibiotic Guardian campaign through the PQS in 2020/21, which was an important first step to ensure the workforce had the necessary capabilities before introducing the TARGET Antibiotic Checklist the following year.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up questionnaire hosted on SnapSurvey (Snap11 professional) collected feedback from a sample of staff about their experience of using the TARGET Antibiotic Checklist as part of the 2021/22 PQS ( Supplementary file S2 ). Questions were based on a previously published evaluation and were co-designed and piloted with pharmacists [ 10 ]. The survey was open from July to October 2022.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations